2006
DOI: 10.1089/cap.2006.16.273
|View full text |Cite
|
Sign up to set email alerts
|

Psychotropic Medication Utilization in a Child and Adolescent Mental Health Service

Abstract: Use of psychotropic medication is frequent in this population. Future research should initially focus on inpatients and intensive treatment settings and examine both safety and efficacy of interventions for depression in young people, atypical antipsychotics for behavioral disturbances, and polypharmacy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
40
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(49 citation statements)
references
References 37 publications
9
40
0
Order By: Relevance
“…The frequency of treatment with psychotropic drugs in this study (46%) was similar to or lower than that in other studies [1][2][3][4]. A large proportion of the patients in our study had learning disorders and almost half of the patients were treated in a partial hospitalisation facility.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The frequency of treatment with psychotropic drugs in this study (46%) was similar to or lower than that in other studies [1][2][3][4]. A large proportion of the patients in our study had learning disorders and almost half of the patients were treated in a partial hospitalisation facility.…”
Section: Discussionsupporting
confidence: 81%
“…Several reviews have examined patterns of psychotropic drug use [1][2][3][4][5]. All suggest that the frequency of psychotropic drug use in these patients is high (43-98% of inpatients were prescribed psychotropic medication).…”
Section: Introductionmentioning
confidence: 99%
“…The burden of ''off label'' use and the small pool of information on the therapeutic dosage and adverse events may limit the use of clozapine despite its clinical benefits in VEOS (Cirulli, 2005;Findling et al, 2007;Kranzler et al, 2006). For Asian population, there is even fewer data on the pediatric use of clozapine (Dean et al, 2006). This study suggested that clozapine could allow the child and adolescent patients suffering from very severe form of refractory schizophrenia to return to their families and the community, improving psychosocial adjustment and long-term outcome of the patients, as was reported in the previous studies of non-Asian patients (Findling et al, 2007;Sporn et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Gerbino-Rosen et al (2005) reported 13% neutropenia and 0.6% agranulocytosis in 172 hospitalized children and adolescents treated with clozapine. However, little is known about the long-term use of clozapine in Asian children and adolescents suffering from EOS (Dean et al, 2006), despite evidences that interethnic differences exist in therapeutic dosage, clinical response, and side effects of clozapine (Matsuda et al, 1996;Subramaniam et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Previous research conducted with youth in non-residential settings has indicated that both clinical (e.g., DSM-IV diagnoses, levels of problem behavior) and non-clinical (e.g., ethnicity, insurance status) factors have been associated with the use of psychotropic medications (Dean et al 2006;Martin et al 2003;Pavkov and Walrath 2008); however, it is not understood why some youth may be prescribed only one psychotropic medication while others may be prescribed more. It has been suggested that physicians may prescribe multiple medications to address complex symptoms or disorders or to treat youth with multiple diagnoses (Safer et al 2003), issues that are particularly relevant for many youth in residential treatment (Duppong Hurley et al 2009).…”
Section: Introductionmentioning
confidence: 99%